THE POLITICS OF COLOR IN HISTORICAL FILMS: CULTURAL DUALITIES IN PADMAAVAT AND BAJIRAO MASTANI - Samanta, Tanmay; Rawat, Ramesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Historical cinema in India frequently transcends mere amusement, serving as a conduit for the formation of cultural memory, political identity, and social values. Sanjay Leela Bhansali's Bajirao Mastani (2015) and Padmaavat (2018) are two great instances of films where visual grandeur is interwoven with ideological narratives. The significance of this study lies in its focus on color as a cinematic language that both preserves and reimagines history. This study examines the impact of chromatic choices on the portrayal of cultural dualities, thereby contributing to broader discussions regarding politics, religion, and identity in Indian cinema. The study is based on Postcolonial Theory, which looks at how the self and other are made in cultural texts, and Social Semiotics, which examines color as a way of communicating that has many meanings. The study aims to examine how Bhansali uses color to depict ideological conflicts, to analyze how visual palettes create cultural dualities, and to evaluate the influence of clothing and set design on the construction of historical narratives. The method uses both descriptive analysis and discourse analysis. The results show that color in Bhansali's films is more than just decoration; it is a political and cultural code that reinterprets history, shapes identities, and embeds ideological stances in spectacle.